The legal aid market : challenges for publicly funded immigration and asylum legal representation / Jo Wilding. - Wilding, Jo, 1974- (Policy Press, 2021)
Presenting a rare picture of the barristers, solicitors and caseworkers practising immigration law in charities and private firms, this book offers fresh thinking on what has gone wrong in the legal aid market. In doing so, this book examines supply and demand, challenges existing legal aid policy and proposes insights for steps forward.